Migrant children and youth : wellbeing and integration around the world - Bass, Loretta (Emerald Publishing Limited, 2025)
This volume contains an Open Access Chapter. Migration represents a challenge and opportunity. Among the world's migrants are nearly 34 million refugees and asylum seekers; of these, half are estimated to be children. As the world struggles to cope with global economic imbalances, diverging demographic trends, and climate change, international and internal migration are increasingly salient for the wellbeing, social integration, and civil and human rights of children and youth. Migrant Children and Youth includes research contributions that illuminate and engage with children and youth as migrants. Featuring chapters from a global and diverse collection of authors, the chapters provide empirical insights from a global perspective of children and youth who are affected by migration processes. Examining root causes and agency, the authors ask, what extent do children and youth exercise volition in the decision to migrate either internally or internationally? From their vantage points to what extent are children and youth on the move, uprooted, and vulnerable? Upon resettlement, what are the social integration challenges and opportunities for children or youth, and to what extent are children and youth migrants constrained in this new context? What do children and youth experience because of migration, and what does this mean for their wellbeing, social integration, and rights?
Keywords: Refugee children.; Children -- Social Conditions -- Cross-cultural studies.; Immigrant children.; Social Science -- Emigration & Immigration.; Childrens, Teenage social topics: Migration, refugees.; Migration, immigration and emigration.; elektronické knihy; electronic books